Case of drug-induced interstitial lung disease secondary to adalimumab. (15th May 2018) - Alaee, Seema; Jones, Quentin
Abstract : We report a rare case of drug-induced intestinal lung disease (ILD) secondary to adalimumab, a tumour necrosis factor alpha-receptor blocker. A 52-year-old smoker with ankylosing spondylitis, treated with adalimumab, presented with progressive breathlessness. A high resolution CT chest demonstrated predominantly upper-zone patchy ground glass changes and small bilateral pleural effusions. Bronchoscopy and bronchoalveolar lavage showed no evidence of infection or malignant cells and an echocardiogram was normal. The working diagnosis was that of possible adalimumab-induced ILD. Adalimumab was subsequently stopped. The patient's breathlessness and cough improved on cessation of the drug. A further CT chest several months later showed resolution of the ground glass changes. Adalimumab-induced ILD is rare. We review the literature surrounding this and discuss the diagnostic challenges. This case highlights the importance of considering the possibility of drug-induced lung disease in patients taking adalimumab.